Depression Is Associated With More Aggressive Inflammatory Bowel Disease. (January 2018) - Kochar, Bharati; Barnes, Edward L; Long, Millie D; Cushing, Kelly C; Galanko, Joseph; Martin, Christopher F; Raffals, Laura E; Sandler, Robert S
Abstract : OBJECTIVES: Depression is prevalent in inflammatory bowel disease (IBD) patients. The impact of depression on IBD is not well‐studied. It is unknown how providers should assess depression. METHODS: We used data from the Sinai–Helmsley Alliance for Research Excellence cohort, to assess methods of diagnosing depression and effects of baseline depression on disease activity at follow‐up. A patient health questionnaire (PHQ‐8) score ≥5 was consistent with mild depression. Relapse was defined as a modified Harvey–Bradshaw Index ≥5 or Simple Clinical Colitis Activity Index >2. We performed binomial regression to calculate adjusted risk ratios (RRs). RESULTS: We included 2, 798 Crohn's disease (CD) patients with 22‐month mean follow‐up and 1, 516 ulcerative colitis (UC) patients with 24‐month mean follow‐up. A total of 64% of CD patients and 45% of UC patients were in remission at baseline. By self‐report, 20% of CD and 14% of UC patients were depressed. By PHQ‐8, 38% of CD and 32% of UC patients were depressed ( P <0.01). Adjusted for sex, remission, and disease activity, CD patients with baseline depression were at an increased risk for relapse (RR: 2.3; 95% confidence interval (CI): 1.9–2.8), surgery, or hospitalization (RR: 1.3 95% CI: 1.1–1.6) at follow‐up. UC patients with baseline depression were also at increased risk for relapse (RR: 1.3; 95% CI: 0.9–1.7), surgery, or hospitalization (RR: 1.3; 95% CI: 1.1–1.5) at follow‐up. CONCLUSIONS: Baseline depression is associated with a higher risk for aggressive IBD at follow‐up. A single question is not a sensitive method of assessing depression. Providers should consider administering the PHQ‐8 to capture those at greater risk for aggressive disease.